2005
DOI: 10.1103/physreve.71.021403
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced charge separation and storage in titanium oxide gels

Abstract: We report on the interaction of light with a particular class of media--wet gels, which in contrast to sols of nanoparticles possess a macroscopic bulk structure, and which differ from conventional solids by the existence of the internal liquid-solid interface. We show, taking an absorption cross section of trapped electrons from Safrany, Gao, and Rabani [J. Phys. Chem. B 104, 5848 (2000)], that a separation of charges with quantum efficiency as high as 46% appears under the band-gap irradiation of titanium ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 30 publications
11
68
0
Order By: Relevance
“…Kuznetsov et al [540] observed a broad absorption continuum for trapped electrons that spanned the range from 350 nm to 2.5 µm.…”
Section: Electron Trappingmentioning
confidence: 98%
See 1 more Smart Citation
“…Kuznetsov et al [540] observed a broad absorption continuum for trapped electrons that spanned the range from 350 nm to 2.5 µm.…”
Section: Electron Trappingmentioning
confidence: 98%
“…Various research groups [133,488,495,506,508,509,[536][537][538][539][540] have determined electron trap lifetimes over a wide timescale (from hundreds of picoseconds [488] to months [540]) as a result of (intentional or unintentional) manipulation of hole scavenger concentrations. For example, Peiró et al [509] used ethanol as a hole scavenger to study electron trapping in synthesized nanocrystalline TiO 2 films, and in films of commercial P-25 and P-90 (which has smaller particles and greater A content than P-25) with transient absorption spectroscopy.…”
Section: Electron Trappingmentioning
confidence: 99%
“…9.3) these absorptions are associated with transitions due to (i) free charge carriers in the mid-infrared (MIR), (ii) excitations of electrons in shallow trap states (MIR-NIR), (iii) d-d transitions of Ti 3+ ions, which are located either in regular or in interstitial lattice sites (Vis) and (iv) the absorption edge due to interband transitions (UV), which may experience a shift to higher energies upon oxide reduction [60]. It is important to note that related spectral signatures have also been observed in TiO 2 after UV light induced charge carrier separation [120], treatment with [60] and on nanocrystal films after cathodic polarization (lower part) [99]. Electron transfer to O 2 and charge extraction upon anodic polarization, respectively, lead to the entire annihilation of all absorption features observed atomic hydrogen [121], injection of radiolytically generated hydrated electrons [122] or, by using a combined spectroscopic and electrochemical approach, upon negative polarization of mesoporous electrodes in aqueous electrolytes (Fig.…”
Section: Optical Absorption and Emissionmentioning
confidence: 95%
“…The amount of trapped electron is generally in the range of one trapped electron per nanoparticle [156]. The trapping of electron is very fast (shorter than 100 fs) while the trapping lifetime is at least in the picoseconds scale and may last several months if no electron scavenger is present [156,157].…”
Section: Charge Carriers Migration and Trappingmentioning
confidence: 99%